AB0867 DEPRESSIVE SYMPTOMS INFLUENCE SUCCESS OF ALLOPURINOL AS URATE LOWERING THERAPY. (June 2019) - Mrug, Sylvie; Orihuela, Catheryn; Rahn, Elizabeth; Saag, Kenneth; Gaffo, Angelo
Abstract : Background: Elevated levels of serum urate (sUA) is the known precursor of gout and urate lowering therapies (ULT) are the backbone of successful gout treatment. However, less is known about factors that influence the effectiveness of ULTs. Depression has shown strong relationships with treatment noncompliance, which may translate into reduced effectiveness of treatment with allopurinol. Little is known about any effects depression may produce on the observed serum urate lowering efficacy of ULTs (e.g.; allopurinol). Objectives: To evaluate the role of depressive symptoms in the efficacy of allopurinol for lowering sUA in the context of a clinical trial. Methods: Within a larger cross-over clinical trial of 300 daily mg of allopurinol vs. placebo for urate lowering and its effect in ambulatory blood pressure (1), 67 patients had complete data for depressive symptoms at the beginning of each treatment period, as well as sUA before and after a 4-week treatment period with allopurinol and a 4-week placebo period (order of conditions was randomized). Depressive symptoms were assessed with the Center for Epidemiologic Studies Depression Scale-10 (CESD-10) (2). Paired samples t-test evaluated change in sUA from pre- to post-treatment during active treatment and placebo. Then, linear regressions predicted change in sUA over each treatment period from pre-treatment depressive symptoms, adjusting for sex and race which were associated with baseline sUA levels. Results: The 67 patients had average age 27.01 years (SD=6.5, range 18-40), 39% were African-American, and 64% were males. Over the 4-week active treatment period, sUA levels decreased from average 5.8 mg/dL (SD=1.2) (345.7 µmol/L) to 4.4 mg/dL (SD=1.2) (261.7 µmol/L), p<.001. However, sUA did not change during the 4-week placebo condition (both 5.8 mg/dL (345.7 µmol/L), SD=1.1 and 1.3, p=0.71). Pre-treatment depressive symptoms ranged from "no symptoms" (0) to "severe symptoms" (16 or 20), with mean in the "no to mild" range (M=4.6, SD=4.1 before active treatment; M=6.1, SD=4.8 before placebo). After adjusting for pre-treatment sUA, sex and race, pre-treatment depressive scores predicted higher levels of sUA at the end of the active treatment period (b=.07, beta=.25, p=.028) but not at the end of the placebo period (b=.03, beta=.11, p=.102). After 4 weeks of allopurinol, the estimated difference in sUA between individuals with pre-treatment depressive scores of 0 vs. 16 was 1.12 mg/dL (66.6 µmol/L), which was similar to the average treatment effect of 1.4 mg/dL (88.3 µmol/L). Conclusion: Even in the absence of clinical diagnosis of depression, depressive symptoms are associated with reduced efficacy of urate-lowering with allopurinol. This could have important implications for gout treatment, as it would suggest that screening for depressive symptoms might be indicated for treatment success. Additional analyses will address whether this effect can be explained by treatment noncompliance. References: [1] Saddekni MB, Saag KG, Dudenbostel T, et al. Contemp Clin Trials. 2016:238-44. [2] Björgvinsson, T., Kertz, S.J., Bigda-Peyton, J.S., McCoy, K.L., Aderka, I.M. Assessment. 2013. 20, 429-436. Disclosure of Interests: Sylvie Mrug: None declared, Catheryn Orihuela: None declared, Elizabeth Rahn: None declared, Kenneth Saag Grant/research support from: Amgen, Ironwood/AstraZeneca, Horizon, SOBI, Takeda, Consultant for: Abbvie, Amgen, Ironwood/AstraZeneca, Bayer, Gilead, Horizon, Kowa, Radius, Roche/Genentech, SOBI, Takeda, Teijin, Angelo Gaffo: None declared